Safety of furazolidone-containing regimen in Helicobacter pylori infection: a systematic review and meta-analysis - Jing Liu; Yan Zhang; Chuan-Guo Guo; Chao-ran Ji; Yue-yue Li; Jun-yan Qu; Xiuli Zuo (BMJ Open, 2020)
Objectives Furazolidone containing regimen is effectivefor Helicobacter pylori (H. pylori) infection, but its safetyremains controversial. To assess the safety of furazolidone containing regimenin H. pylori infection.Design A systematic review and meta-analysis.Data sources PubMed, Embase, Cochrane Library, Web of Science and Scopus databases were systematically searched for eligible randomised controlled trials.Eligibility criteria Studies comparing furazolidone with non-furazolidone-containing regimen, variable durations or doses of furazolidone were included.Data extraction and synthesis Two reviewers independently selected studies and extracted data. Primary outcomes were the risk of total adverse events (AEs), serious AEs and severe AEs, expressed as relative risk (RR) with 95% CI. Secondary outcomes contained the incidence of individual adverse symptoms, AE-related treatment discontinuation and compliance.Results Twenty-six articles were identified from 2039 searched records, of which 14 studies (n=2540) compared furazolidone with other antibiotics. The eradication rates of furazolidone-containing regimen were higher than those of other antibiotics in both intention-to-treat (RR 1.06, 95% CI 1.01 to 1.12) and per-protocol analysis (RR 1.05, 95% CI 1.00 to 1.10). Only two serious AEs were reported in furazolidone group (2/1221, 0.16%). No significant increased risk was observed for the incidence of total AEs (RR 1.04, 95% CI 0.89 to 1.21) and severe AEs (RR 1.81, 95% CI 0.91 to 3.60). Twelve studies (n=3139) compared different durations of furazolidone, and four studies (n=343) assessed variable doses. Elevated risk of total AEs and severe AEs were only found in a high daily dose of furazolidone rather than prolonged duration. The incidence of AE-related treatment discontinuation and compliance of patients were all similar, irrespective of dose and duration adjustments.Conclusion Furazolidone-containing regimen has a similar risk of AEs and compliance as non-furazolidone-containing regimen. A low daily dose of 200 mg is well-tolerated for 14 day regimen and should be first considered.PROSPERO registration number CRD42019137247